Variations in Hate Crime Cases by Bias Motivation Type: Findings From the National Hate Crime Investigation Study (NHCIS) - Turner, Heather A. (Crime & delinquency, 2025)
Accurate and detailed information on the nature of hate crimes in the United States has been hindered by limitations in the compiling of hate crime statistics. The National Hate Crime Investigation Study (NHCIS) collected data from a nationally representative sample of law enforcement agencies across the U.S. about the numbers of hate crimes investigated during 2018. Results show differences in a variety of case characteristics across four major categories of bias motivation (race/ethnicity, religion, sexual orientation/gender identity, and disability). Results suggest that police may miss hate crimes with bias motivations that are not clearly connected to common culturally recognized indicators. Training around non-stereotypical hate crime cases may help to identify and strengthen hate crime evidence.